Healthy Living: Change your Lifestyle Word Scramble - Linda B. Bobroff; Valerie Weyenberg (EDIS)
Many people know that it is important to eat healthy foods to control and even prevent high blood pressure. But did you know there are other things you can do to help keep it down? This 1-page fact sheet is a minor revision written by Valerie Weyenberg and Linda B. Bobroff, and published by the Department of Family, Youth and Community Sciences, February 2017.